Processus de métropolisation dans l’espace frontalier post-soviétique : l’exemple de Rostov-sur-le-Don - Clémentine Cottineau (Cybergeo, 2011)
This paper focuses on the process of metropolization in Russia, through an illustration: the border city of Rostov-on-Don. Our purpose is to determine if the city participates in the current metropolization process, and with which system it interacts most intensely (European, national or regional system of cities). Considering the border situation of Rostov-on-Don leads to an evaluation of pluses and minuses that this border represents regarding the perspectives of integration in the European system of cities.